Phytoplasma of 16SrVII-B subgroup associated to shoot proliferation in Physalis peruviana plants - Jacson Ferreira; Cláudia Alves de Almeida; Felipe Franco de Oliveira; Arnaldo Fariña; Elliot Watanabe Kitajima; Ivan Paulo Bedendo (Scientia Agricola, 2021)
ABSTRACT: Physalis is an herbaceous species native to the Andes region. Currently, it is cultivated in various Brazilian states due to the economic interest of growers for this new fruit. Physalis plants grown in the field showed symptoms of shoot proliferation, leaf malformation, and chlorosis. Since these symptoms are commonly induced by phytoplasmas, this study investigated to confirm the presence of these prokaryotes in symptomatic plants. After DNA extraction from symptomatic and asymptomatic plants, phytoplasmas were found in all affected plants through the nested PCR. Examination by transmission electron microscopy (TEM) using appropriately prepared segments of leaf veins allowed the visualization of typical pleomorphic cells of phytoplasmas in the phloem of symptomatic plants. The computer-simulated RFLP patterns and the phylogenetic analysis allowed identifying the detected phytoplasmas as a ‘Candidatus Phytoplasma fraxini’-related strain belonging to the 16SrVII-B subgroup. Moreover, physalis was identified as an additional host species for phytoplasmas in the 16SrVII group, expanding the current knowledge on the host range of phytoplasmas in this group.